Coherent transient spectroscopy with continuous wave quantum cascade lasers. - Kirkbride, J; Causier, S; McCormack, E; Weidmann, D; Ritchie, G (2013)
A high power continuous wave quantum cascade laser operating around 1900 cm(-1) has been used to conduct Lamb dip spectroscopy on a low pressure sample of NO. The widths of the Lamb dips indicate that the laser linewidth is 800 ± 60 kHz and the power sufficient to induce significant population transfer of up to 35%. While the Lamb dip signals are symmetric at low laser chirp rates, they become increasingly asymmetric as the chirp rate increases, further confirming the significant degree of population transfer. In addition rapid passage structure on the Lamb dip signal is observed after the weak probe beam is swept through the line center. This structure is sensitive to both the probe chirp rate and the underlying hyperfine structure of the rovibrational transition, and is accurately modeled using the optical Bloch equations.